Xanthan gum and Locust bean gum gel supports in vitro development of porcine oocytes derived from early antral follicles - Yasuhisa MUNAKATA; Ayaka SUGIMOTO; Koumei SHIRASUNA; Takehito KUWAYAMA; Hisataka IWATA (The Society for Reproduction and Development, 2019)
Early antral follicle (EAF)-derived porcine oocytes develop more readily on polyacrylamide-gel (PAG) than on plastic plates. Xanthan gum (XG) and locust bean gum (LBG) are edible polysaccharides. We investigated XG-LBG gel supports in the development of EAF-derived porcine oocytes. XG and LBG were mixed in a 1:1 ratio to form a substrate. We cultured oocyte granulosa cell complexes (OGCs) from the EAFs on XG-LBG gels of various concentrations. The oocyte diameters were comparable among the 0.3, 0.5, and 1.0% gels; granulosa cell proliferation was greater on the 1.0% gel. The proliferation and survival rates of the granulosa cells, and the histone H4 at lysine 12 acetylation levels were higher in OGCs cultured on 1.0% XG-LBG than those grown on 0.3% PAG. Development to the blastocyst stage was 13.8% for the XG-LBG gels and 9.4% for PAG. In conclusion, XG-LBG are safe and efficient substrates for in vitro culture of oocytes.